Use of autobiographical stimuli as a mood manipulation procedure: Systematic mapping review. - Fernández-Pérez, Dolores; Toledano González, Abel; Ros, Laura; Latorre, José Miguel (Plos One, 2022)
Background In recent years, mood induction procedures have been developed in experimental settings that are designed to facilitate studying the impact of mood states on biological and psychological processes. The aim of the present study was to conduct a systematic mapping review with the intention of describing the state of the art in the use of different types of autobiographical stimuli for mood induction procedures. Methods Based on a search for publications from the period 2000–2021, conducted in four recognised databases (Scopus, Medline (PubMed), PsycINFO and Web of Science), we analysed a total of 126 published articles. Text mining techniques were used to extract the main themes related. Results The induction of emotions through autobiographical memories is an area under construction and of growing interest. The data mining approach yielded information about the main types of stimuli used in these procedures, highlighting those that only employ a single type of cue, as well as the preference for verbal cues over others such as musical, olfactory and visual cues. This type of procedure has been used to induce both positive and negative emotions through tasks that require access to personal memories of specific events from a cue, requiring the person to set in motion different cognitive processes. The use of the latest technologies (fMRI, EEG, etc.) is also shown, demonstrating that this is a cutting-edge field of study. Conclusions Despite the study of mood induction procedures still being a growing field, the present review provides a novel overview of the current state of the art in the field, which may serve as a framework for future studies on the topic.
Keywords: Emociones y sentimientos; Autobiographical Stimuli; Mood; Manipulation Procedure; Mood Induction